Phenotypic differences of mutation‐negative cases in Gitelman syndrome clinically diagnosed in adulthood. Issue 3 (31st December 2020) - Mori, Takayasu; Chiga, Motoko; Fujimaru, Takuya; Kawamoto, Ryosuke; Mandai, Shintaro; Nanamatsu, Azuma; Nomura, Naohiro; Ando, Fumiaki; Susa, Koichiro; Sohara, Eisei; Rai, Tatemitsu; Uchida, Shinichi
Abstract: Gitelman syndrome (GS), an autosomal recessive kidney disorder, is characterized by hypokalemia, hypomagnesemia, hypocalciuria, and metabolic alkalosis. Generally, diagnosis is made in school‐aged children but multiple cases have been diagnosed in adulthood. This study examines the phenotypic differences between genetically confirmed cases and mutation‐negative cases in adults. A comprehensive screening of 168 genes, including GS‐related genes, was performed for 84 independent individuals who were referred to our institute with a clinical diagnosis of GS. The cases of pseudo‐Bartter syndrome (BS)/GS because of diuretic abuse or other causes, which was determined based on patients' medical records, were excluded during registration. Of these 70 eligible cases for analysis, 27 (38.6%) had genetic confirmation of GS, while 37 (52.8%) had no known variants associated with GS and were considered to be unsolved cases. Note that unsolved cases comprised older, mostly female, individuals with decreased kidney function and multiple basic features of GS. The phenotype of unsolved cases is similar to that of pseudo BS/GS cases, although these cases were excluded in advance. However, the genetic and autoimmune profiles of these unsolved cases have not yet been investigated to date. Therefore, these cases may be categorized into new disease groups. Abstract : Mutations detected in the study and mutations previously reported as hotspots in SLC12A3 . In our cohort, 27 (38.6%) patients had genetic confirmation of GS, while 37 (52.8%) had no causal variants associated with GS.